PENINGKATAN PERKEMBANGAN BAHASA ANAK USIA DINI MELALUI METODE BERMAIN PERAN - Resi Faizah Noviyanti; Saeful Millah (Tarbiyat al-Aulad: Jurnal Pendidikan Islam Anak Usia Dini, 2019)
The purpose of this study is to determine the learning process in improving language development through role playing methods, can improve children's language development. The research method used was classroom action research. Data collection techniques used are observation and assessment techniques. The conclusions obtained from this study are: 1) The ability of teachers in preparing learning plans has increased. This can be seen from the results of observations on the ability of teachers in preparing learning plans, namely in the first cycle reached a value of 2.37 (59%) and the second cycle reached a value of 3.37 (84%). 2) The ability of teachers in implementing learning has increased. This can be seen from the results of observations on the ability of teachers in the learning process, which in the first cycle reached a value of 2.49 (62%) and the second cycle reached a value of 3.55 (89%). 3) There is an increase in language skills. This can be seen from the assessment of student learning outcomes, namely in the first cycle the number of children who developed according to expectations there were 6 children (30%) in the second cycle increased to 13 children (65%), while in the first cycle the number of children who developed very well there 1 child (5%) in the second cycle increased to 4 children (20%).